Bidisperse bulk materials in chemical engineering - Vytiahanets, Valentyn; Pitak, Inna; Bairachnyi, Volodymyr (BoScience Publisher, 2023)
Bidisperse bulk materials, consisting of two distinct particle sizes, have gained significant attention in the field of chemical engineering due to their unique properties and potential applications. This literature review aims to explore the current state of research on bidisperse bulk materials, focusing on their synthesis, characterization, and various applications in chemical processes. The review also discusses the challenges and future prospects associated with the utilization of bidisperse materials in chemical engineering.
Keywords: materials; sizes; bidisperse; calcium carbonate; chemical engineering